Efficacy of transumbilical laparoendoscopic single-site surgery versus multi-port laparoscopic surgery for endometrial cancer: a retrospective comparison study - You, Xiaolin; Wang, Yanyun; Zheng, Ying; Yang, Fan; Wang, Qiao; Min, Ling; Wang, Kana; Wang, Na (Frontiers in Oncology, 2023)
Background: Although single-port laparoscopy surgery has been evaluated for several years, it has not been widely adopted by gynecologic oncologists. The objective was to compare the perioperative outcomes and survival of endometrial cancer (EC) patients undergoing transumbilical laparoendoscopic single-site surgery (TU-LESS) with multi-port laparoscopic surgery (MLS).This is a retrospective comparative monocentric study including patients treated between December 2017 and October 2021. The perioperative outcomes and survival of EC patients who had surgery via TU-LESS or MLS were compared, by propensity matching.Results: A total of 156 patients were included (TU-LESS vs. MLS: 78 vs. 78). The conversion rate of TU-LESS and MLS was 5.13% and 2.56%, respectively (P=0.681). The operation time was comparable between the two groups [207.5min (180-251) vs. 197.5min (168.8-225), P=0.095]. There was no significant difference between the two groups in exhaustion time, perioperative complications, or postoperative complications. While, the TU-LESS group had a shorter out-of-bed activity time [36 hours (24-48) vs. 48 hours (48-72), P<0.001] and a lower visual analog pain scale 36 hours after surgery [1 (1-2) vs. 2 (1-2), P<0.001] than the MLS group. The length of hospital stay was similar in the two groups [5(4-6) vs. 5(4-5), P=0.599]. Following surgery, 38.5% of the TU-LESS patients and 41% of the MLS patients got adjuvant therapy (P=0.744). The median follow-up time for TU-LESS and MLS cohorts was 45 months (range: 20-66) and 43 months (range: 18-66), respectively. One TU-LESS patient and one MLS patient died following recurrence. The 4-year overall survival was similar in both groups (98.3% vs. 98.5%, P=0.875).TU-LESS is a feasible and safe option with comparable perioperative outcomes and survival of MLS in endometrial cancer. With the growing acceptance of sentinel lymph node biopsy, TU-LESS of endometrial cancer may be a viable option for patients and surgeons. 9 This project is a retrospective investigation study. All patients involved have provided informed consent. The Ethics Committee of our hospital approved this research, and the validity period is from